Keberlanjutan Penerapan Teknologi Padi Sawah Ramah Lingkungan dalam Aspek Kapasitas Petani dan Sifat Inovasi di Sulawesi Tengah - Rahayu, Heni Sulistyawati Purwaning; Herawati (Jurnal Penyuluhan, 2021)
Friendly environment lowland rice management is an alternative way which can be implemented by farmers for getting a balance and sustainability of environment. However, challenges often faced by environmentally friendly agriculture such as the sustainability of its application after the technological innovation was disseminated. Some factors are thought to influence the sustainability of friendly environment rice management namely capacity of farmers and the nature of technology innovation. This study aims to determine the relationship between farmer capacity and the nature of innovation on the sustainability of the application of environmentally friendly rice technology in Central Sulawesi. Data collection was carried out through a survey using a questionnaire to 174 respondents. Data were analyzed descriptively and statistically quantitatively using multinomial logit regression. The results of the analysis show that the capacity of farmers and the nature of innovation that significantly affects the sustainability of the application of environmentally friendly lowland rice technology in Central Sulawesi is the relative cost advantage, relative price advantage, complexity in application, evaluation of farming, and knowledge of environmentally friendly lowland rice management. Therefore, there is a need to increase all significant variabels and to expand the dissemination of innovations in environmentally friendly lowland rice technology.